Let's analyze Lily's work step by step to understand the implications of her partial solution.
Starting from her equation: \[ 4(x - 1) - x = 3(x + 5) - 11 \]
She correctly expanded both sides: \[ 4x - 4 - x = 3x + 15 - 11 \] which can be simplified to: \[ 4x - x - 4 = 3x + 15 - 11 \] \[ 3x - 4 = 3x + 4 \]
Next, when she reaches: \[ 3x - 4 = 3x + 4 \]
Notice that both sides have the term \( 3x \). If we subtract \( 3x \) from both sides, we are left with: \[ -4 = 4 \]
This is a contradiction, meaning that there are no values of \( x \) that satisfy the original equation. Therefore, the interpretation of her partial solution indicates that:
The equation has no solution.